An APEC Trade Agenda? : The Political Economy of a Free Trade Area of the Asia-Pacific - Pedrosa, Eduardo; Morrison, Charles Edward, 1944- (Book collections on Project MUSE., 2007)
Assesses the political feasibility of the Free Trade Area of the Asia-Pacific (FTAAP) proposal and looks at alternative modalities for achieving free trade and investment in the Asia-Pacific.